2011
DOI: 10.1167/iovs.10-6187
|View full text |Cite|
|
Sign up to set email alerts
|

Corneal Endothelial Toxicity of Air and SF6

Abstract: These results indicate that both air and SF6 injected into the anterior chamber of the eye can induce intraocular reaction in the feline model and that SF6 is more toxic than air in terms of endothelial cell loss and anterior chamber inflammation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
35
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(38 citation statements)
references
References 30 publications
1
35
0
2
Order By: Relevance
“…Same-day complete air removal may help prevent graft detachment by restoring the aqueous to the endothelial cells, facilitating endothelial pump function and graft adhesion. In addition, air bubble-induced endothelial toxicity and trauma have been reported in previous studies 12,13 and may participate in higher rates of graft detachment.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…Same-day complete air removal may help prevent graft detachment by restoring the aqueous to the endothelial cells, facilitating endothelial pump function and graft adhesion. In addition, air bubble-induced endothelial toxicity and trauma have been reported in previous studies 12,13 and may participate in higher rates of graft detachment.…”
Section: Discussionmentioning
confidence: 70%
“…3,15 In addition, as previously mentioned, the air bubble has been implicated in causing endothelial toxicity and trauma. 12,13 Removing all residual air after surgery prevents the risk of air bubble-induced pupillary block glaucoma and may decrease the risk of air bubble-associated endothelial trauma.…”
Section: Discussionmentioning
confidence: 99%
“…On a similar note, a recent study compared intracameral air and SF 6 in a feline model and found that prolonged SF 6 contact with the corneal endothelium may cause increased inflammation and pronounced endothelial cell loss in the superior area. 24 However, there are no reports of toxicity with short-term use at nonexpansile concentrations. In our study, the percentage of loss of corneal endothelial cells was similar in both groups (30AE11% for SF 6 vs. 32AE13% for 100% air), which is in accordance with other studies on DMEK.…”
Section: Discussionmentioning
confidence: 99%
“…18 However, calcification has also been attributed to breakdown of the blood-aqueous barrier, which might occur after air injection or repeat surgery. 19 Further investigation will be necessary to determine whether IOL opacifications are the result of the intracameral air, by direct contact with the surface of the IOL or by inducing metabolic changes in the anterior chamber, or of an exacerbated inflammatory reaction leading to breakdown of the blood-aqueous barrier or a combination of both.…”
Section: Discussionmentioning
confidence: 99%